1990
DOI: 10.1021/ja00159a025
|View full text |Cite
|
Sign up to set email alerts
|

Series of two-coordinate and quasi-two-coordinate transition-metal complexes: synthesis, structural, and spectroscopic studies of sterically demanding borylamide ligands -NRBR'2 (R = Ph, R' = Mes, Xyl; R = R' = Mes), their lithium salts, Li(Et2O)2NRBR'2, and their transition-metal derivatives, M(NPhBMes2)2 (M = Cr, Co, Ni), Co(NPhBXyl2)2 and M(NMesBMes2)2 (M = Cr .fwdarw. Ni)

Abstract: ChemInform Abstract Amide ligands (I) (preparation described) and (III), modified by the presence of the diarylboryl substituents, are used to synthesize low-coordinate metal complexes of unusual structure. X-ray analyses are carried out for (IIIa) (P1, Z=2), (VIa) (Pbca, Z = 8), (VIIIb) (P21/c, Z=4), (Xa), (XI) and (XIIa) (all P1, Z=2). The transition-metal complexes are all high-spin with nominally two-coordinate geometries. However, they all display some deviation from linearity, the strongest N-M-N bending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
80
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 0 publications
7
80
1
2
Order By: Relevance
“…Table 7 (62). For the molecular compounds, longer Co-N bond distances decrease the overlap of atomic orbitals.…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
“…Table 7 (62). For the molecular compounds, longer Co-N bond distances decrease the overlap of atomic orbitals.…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
“…Careful crystallization of this mixture resulted in the isolation and structural characterization of both major products.W hile product 2 is confirmed to be the isocyanate adduct Ph2tBuAr N/B-FLP( Ph2tBu ArNCO) of the bulky isocyanate/FLP pair (see Figure S9 in the Supporting Information), the unsymmetrical product 3 is the unanticipated, rearranged aminoborane isomer of the targeted Ph2tBuAr N/B-FLP.T he Xray crystal structure of 3 (Scheme 2b)displays an alternative coordination motif for this FLP with ac ovalent BÀNb ond (N1-B1 = 1.4124 (19) )a nd af ree formamide moiety (C1-O1 = 1.2007(17) )t hat conceptually results from hydroboration of the hindered N = Cbond of the isocyanate.This B À N bond is typical of borylamides R 2 B-NR 2 . [20][21][22][23][24] TheB-N-C(H) = Oa toms essentially lie in one plane (B1-N1-C1-O1 = 170.68 8) consistent with adelocalized p system involving the carbonyl C=Od ouble bond in conjugation with the N!B p interaction. TheI Rs pectrum displays ab and at 1647 cm À1 corresponding to the C = Os tretch at ab it lower energy than in unconjugated formamides such as HC(O)NMe 2 (1675 cm À1 ).…”
mentioning
confidence: 99%
“…[2] TheM n, Fe,a nd Co silylamides are thermally stable and have proven to be valuable synthons in diverse applications, [4][5][6][7][8][9][10][11][12][13] but the unstable nature of Ni{N(SiMe 3 ) 2 } 2 has hindered its further use.I ts instability is especially striking because several other stable,h omoleptic Ni II amides are known. These include {Ni(NPh 2 ) 2 } 2 , [14] the borylamides Ni{N(R)BMes 2 } 2 (R = Ph or Mes), [15,16] the primary terphenyl amides Ni{N(H)Ar Me6 } 2 , [17] Ni{N(H)Ar iPr4 } 2 , [18] and Ni{N(H)Ar iPr6 } 2 [17] (Ar Me6 = C 6 H 3 -2,6-(C 6 H 2 -2,4,6-Me 3 ) 2 , Ar iPr4 = C 6 H 3 -2,6(C 6 H 3 -2,6-i Pr 2 ) 2 ,A r iPr6 = C 6 H 3 -2,6(C 6 H 2 -2,4,6-i Pr 3 ) 2 ), and Ni{N(SiMe 3 )Dipp} 2 (Dipp = C 6 H 3 -2,6-i Pr 2 ). [19,20] Computations indicated that the latter and its Fe and Co analogues are probably stabilized by attractive interligand dispersion forces.…”
mentioning
confidence: 99%